The major histocompatibility complex-restricted antigen receptor on T cells. I. Isolation with a monoclonal antibody (The Rockefeller University Press, 1983)
An antibody-secreting B cell hybridoma, KJ1-26.1, has been prepared from mice immunized with the T cell hybridoma DO-11.10, which recognizes chicken ovalbumin in association with I-Ad (cOVA/I-Ad). KJ1- 26.1 blocks I-restricted antigen recognition by DO-11.10 and a subclone of this T cell hybridoma, DO-11.10.24, which has the same specificity for cOVA/I-Ad as its parent. KJ1-26.1 does not block I-restricted antigen recognition by any other T cell hybridoma tested, including a number of T cell hybridomas closely related to DO-11.10, with similar, but not identical, specificities for antigen/I. Moreover, KJ1-26.1 binds to DO-11.10 and DO-11.10.24, but not to any other T cell hybridomas tested, including three subclones of DO-11.10 that have lost the ability to recognize cOVA/I-Ad. Thus, in every regard KJ1-26.1 appears to be binding to all or part of the receptors for antigen/I on the T cell hybridoma DO-11.10. KJ1-26.1 appears to bind to approximately 15,000 molecules/cell on the surface of DO-11.10. The antibody precipitates an 80,000 dimer from the cells, which on reduction migrates as 40-44,000 monomers. The receptor(s) for antigen/I on DO-11.10 therefore includes molecules with these properties.